Enhanced newspaper subscriptions payment platform - Karimbika, Tapiwa Wilfred (Midlands State University, 2019)
The drive behind development of The Patriots web based payment platform and marketing tool was to provide Zimbabwe Heritage Trust with a technological solution to market their authored books and to facilitate convenient fund transactions for customers and the organisations marketing department. The enhanced newspaper subscriptions payment platform project will provide benefits for the organisation by implementing a computerised system of the manual subscription process being used currently in the marketing department. The platform will allow for centralised data storing using the MySQL database, providing data integrity in the system. Zimpapers distributers of the newspaper will also be included in the system access levels so that they can receive client distribution details automatically. Payment notifications are an included functionality of the system to engage users with the system. For development of the system to be successful, findings and analysis of the user requirements were obtained through various methodologies and communication forms. Based on the requirements revealed, planning of the project was done by carrying out feasibility studies to certify the project as economically, technically and operationally feasible. Analysis of the system was also done to compare the weaknesses of the manual subscription system that was used in the organisation and the payment platform. This analysis was done with the aid of visual diagrams. Design of the system was then carried out to provide the best user interfaces for user-system interaction before the enhanced newspaper subscriptions payment platform was then implemented into the working environment. Parallel changeover was defined as the best method of installation as running both the computerised system and manual system would not clash and allow for backup of data. In future, other modules can be added to the system like developing on the payment platform for subscribing for advertising space.